Motivasi Belajar Mahasiswa Pada Pembelajaran Jarak Jauh Dalam Jaringan Mata Kuliah Menulis Bahasa Mandarin - Hasan; Rahmi, Pramawati Andaru; Zelia, Vanya (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2023)
In order to stop the spread and transmission of Covid-19, the Ministry of Education and Culture of Republic Indonesia has changed the learning system in Indonesia from face-to-face to distance learning, one of which is online distance learning. The implementation of online distance learning has limitations that affect the enthusiasm and motivation to learn. This study is conducted to describe student learning motivation, with a focus on the intrinsic motivation of students of the Department of Chinese Language Education State University of Jakarta (PSPBM UNJ) in online distance learning Basic Writing Courses. The data collection technique in this study adopted a Likert scale survey method and distributed by Google Form Intrinsic motivation theory in this study is based on Fitriyani's theory which is developed into 7 indicators, those are concentration, curiosity, enthusiasm, independence, readiness, never give up, and self-confidence. Respondents are 46 students who took Basic Writing Courses level 1 to 4 at PSPBM UNJ.. The results of the study show: (1) students can concentrate during lesson in class; (2) students have a curiosity about the material that will be delivered during lesson in class; (3) students have enthusiasm when attending class; (4) students have a sense of independence in learning; (5) students are better prepared mentally, compared to prepared physically; (6) students have persistent attitude in learning to write in Chinese; and (7) students have self-confidence during lesson in class.